HUBUNGAN PENGETAHUAN IBU YANG MEMILIKI ANAK PRASEKOLAH DENGAN TINDAKAN PERTOLONGAN PERTAMA PADA CEDERA - Rita Zahara; Novia Rizana; Niken Apdiningsih (Jurnal Assyifa' Ilmu Keperawatan Islami, 2022)
First aid is care given directly to people who are injured or suddenly sick. Injuries to children can be in the form of accidental or unintentional and intentional. Mother’s knowledge about injuries and first aid measures in children is one the influencing factors. The purpose of the study was to determine the relationship between knowledge of mothers who have preschool-aged children and first aid measures for injuries.This study used an analytical design with a cross sectional approach. The number of the sample was 52 respondents using a total sampling technique. The research was carried out on 11 to 15 September 2021. The analysis was carried on by a computerized procces through the chi square test. The results of the statistical test showed that p value = 0.000 <0.05. This reveals that there is a relationship between mother’s knowledge and first aid measures for injuries at Keude Lapang, Gandapura District, Bireuen. Therefore, it is suggested that mothers with preschool children having sufficient and less knowledge regarding first aids should increase their knowledge by participating in counseling and actively exchanging information regarding the issue with the closest people.